2021
DOI: 10.3168/jds.2021-20128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tolC on tolerance to bile salts and biofilm formation in Cronobacter malonaticus

Abstract: Bile salts is one of essential components of bile secreted into the intestine to confer antibacterial protection. Cronobacter species are associated with necrotizing enterocolitis in newborns and show a strong tolerance to bile salts. However, little attempt has been made to focus on the molecular basis of the tolerance to bile salts. In this study, we investigated the roles of tolC on growth, cell morphology, motility, and biofilm formation ability in Cronobacter malonaticus under bile salt stress. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…For the antibiotic resistance genes, all C. sakazakii strains and the C. malonaticus strain exhibited the same efflux, antibiotic inactivation, and antibiotic target alteration genes that confer antibiotic resistance to β-lactams, fluoroquinolones, aminoglycosides, imidazoles, and disinfectants such as triclosan. The marA gene, whose transcription function regulates multidrug efflux, modulates membrane permeability and activates the transcription of the AcrAB-TolC efflux pump that plays an important role in antibiotic resistance ( Wang X. et al, 2021 ). Several authors have detected the msbA , emrR , H-NS , emrB , marA , CRP , PBP3 , H-NS , and msrB genes that are associated with antibiotic resistance by using efflux pumps, regulatory systems, and antibiotic target protection genes ( Aly et al, 2019 ; Lepuschitz et al, 2019 ; Parra-Flores et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…For the antibiotic resistance genes, all C. sakazakii strains and the C. malonaticus strain exhibited the same efflux, antibiotic inactivation, and antibiotic target alteration genes that confer antibiotic resistance to β-lactams, fluoroquinolones, aminoglycosides, imidazoles, and disinfectants such as triclosan. The marA gene, whose transcription function regulates multidrug efflux, modulates membrane permeability and activates the transcription of the AcrAB-TolC efflux pump that plays an important role in antibiotic resistance ( Wang X. et al, 2021 ). Several authors have detected the msbA , emrR , H-NS , emrB , marA , CRP , PBP3 , H-NS , and msrB genes that are associated with antibiotic resistance by using efflux pumps, regulatory systems, and antibiotic target protection genes ( Aly et al, 2019 ; Lepuschitz et al, 2019 ; Parra-Flores et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Acinetobater baumannii, Cronobacter malonaticus, and Bifidobacterium formed more biofilms when exposed to bile salts [118][119][120]. In Bifidobacterium breve, bile-saltinduced biofilm formation involved QS, EPS production and eDNA release, and increased its viability when exposed to porcine bile salts [118].…”
Section: Host-derived Factors and Biofilm Formationmentioning
confidence: 97%
“…In A. baumannii, exposure to bile salts increased expression of virulence factors associated with surface motility, biofilm, and type VI secretion systems, and these are also associated with activation of the QS system [119]. In the case of C. malonaticus, bile salts exposure induced an upregulation of the AcrAB-TolC system, but the molecular mechanisms involved in biofilm formation remain unknown [120].…”
Section: Host-derived Factors and Biofilm Formationmentioning
confidence: 99%
“…Ye et al (2016) found that Sribosylhomocysteinelyase are differentially expressed proteins between biofilm and planktonic cells by two-dimensional gel electrophoresis (2-DE) technique, evidencing that Sribosylhomocysteinelyase may regulate Cronobacter. Cronobacter escaped from the acidic environment by up-regulating flagellar genes, while luxS regulated biofilm formation, adhesion and cellular motility in Cronobacter by negatively regulating flgM, and positively regulating flagellar assembly fliC expression (Wang et al 2021). Cronobacter has strong drying resistance characteristic, allowing it to survive in low-moisture infant formula; luxS also improves the desiccation resistance of Cronobacter.…”
Section: Introductionmentioning
confidence: 99%
“…Cronobacter escaped from the acidic environment by up‐regulating flagellar genes, while luxS regulated biofilm formation, adhesion and cellular motility in Cronobacter by negatively regulating flgM , and positively regulating flagellar assembly fliC expression (Wang et al . 2021). Cronobacter has strong drying resistance characteristic, allowing it to survive in low‐moisture infant formula; luxS also improves the desiccation resistance of Cronobacter .…”
Section: Introductionmentioning
confidence: 99%